Web development with MongoDB and Node : build fast web applications for handling any kind of data - D'Mello, Bruno Joseph; Satheesh, Mithun; Krol, Jason (Packt Publishing, 2017)
Use the two popular web development stacks, Node.js and MongoDB, to build full-featured web applications About This Book Learn the new ECMAScript along with Node 8 and MongoDB to make your application more effective. Get the up-to-date information required to launch your first application prototype using the latest versions of Node.js and MongoDB. A practical guide with clear instructions to designing and developing a complete web application from start to finish using trending frameworks such as angular4 and hapi Who This Book Is For The book is designed for JavaScript developers of any skill level who want to get up-and-running using Node.js and MongoDB to build full-featured web applications. A basic understanding of JavaScript and HTML is the only prerequisite for this book. What You Will Learn Work with Node.js building blocks Write and configure a web server using Node.js powered by the Express.js framework Build dynamic HTML pages using the Handlebars template engine Persist application data using MongoDB and Mongoose ODM Test your code using automated testing tools such as the Mocha framework Automate test cases using Gulp Reduce your web development time by integrating third-party tools for web interaction. Deploy a development environment to the cloud using services such as Heroku, Amazon Web Services, and Microsoft Azure Explore single-page application frameworks to take your web applications to the next level In Detail Node.js builds fast, scalable network applications while MongoDB is the perfect fit as a high-performance, open source NoSQL database solution. The combination of these two technologies offers high performance and scalability and helps in building fast, scalable network applications. Together they provide the power for manage any form of data as well as speed of delivery. This book will help you to get these two technologies working together to build web applications quickly and easily, with effortless deployment to the cloud. You will also learn about angular 4, which consumes pure JSON APOIs from a hapi server. The book begins by setting up your development environment, running you through the steps necessary to get the main application server up-and-running. Then you will see how to use Node.js to connect to a MongoDB database and perform data manipulations. From here on, the book will take you through integration with third-party tools to interact with web apps. You will see how to use controllers and view models ...